Organometallic chemistry--8 : plenary lectures presented at the Eighth International Conference on Organometallic Chemistry, Kyoto, Japan, 12-16 September, 1977 - Ishii, Y.; Hagihara, N. (Pergamon Press, 1979)
Organometallic Chemistry - 8 focuses on the compositions, reactions, properties, and transformations of molecules, silicon carbon, molybdenum and tungsten compounds, palladium, and platinum. The selection first offers information on the theoretical aspects of the coordination of molecules to transition metal centers and generation and reactions of silicon-carbon double-bonded intermediates. Discussions focus on photolysis of naphthyldisilanes, alkenyldisilanes, phenylacetylene, and benzenoid aromatic derivatives of disilane. The book also considers classical and novel ylide systems in organome.